2018
DOI: 10.2196/11322
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between the Use of Electronic Health and the Use of General Practitioner and Somatic Specialist Visits in Patients With Type 1 Diabetes: Cross-Sectional Study

Abstract: BackgroundThe prevalence of diabetes and the use of electronic health (eHealth) are increasing. People with diabetes need frequent monitoring and follow-up of health parameters, and eHealth services can be of great value. However, little is known about the association between the use of eHealth and provider-based health care services among people with diabetes.ObjectiveThe objective of this study was to investigate the use of 4 different eHealth platforms (apps, search engines, video services, and social media… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 43 publications
(63 reference statements)
2
48
0
Order By: Relevance
“…The sensitivity for capturing risk conditions depends on whether all diagnoses on existing conditions are registered during health care visits, and that patients regularly see a doctor for their condition. A Norwegian study in adults found that only 60% of adult patients with diabetes had seen a specialist the last year (42). However, children in Norway with chronic conditions such as diabetes or epilepsy, are very likely to have annual visits and check-ups in specialist care and are thereby expected to be correctly de ned in this registrybased study.…”
Section: Discussionmentioning
confidence: 94%
“…The sensitivity for capturing risk conditions depends on whether all diagnoses on existing conditions are registered during health care visits, and that patients regularly see a doctor for their condition. A Norwegian study in adults found that only 60% of adult patients with diabetes had seen a specialist the last year (42). However, children in Norway with chronic conditions such as diabetes or epilepsy, are very likely to have annual visits and check-ups in specialist care and are thereby expected to be correctly de ned in this registrybased study.…”
Section: Discussionmentioning
confidence: 94%
“…The sensitivity for capturing risk conditions depends on whether all diagnoses on existing conditions are registered during health care visits, and that patients regularly see a doctor for their condition. A Norwegian study in adults found that only 60% of adult patients with diabetes had seen a specialist the last year (43). However, children in Norway with chronic conditions such as diabetes or epilepsy, are very likely to have annual visits and check-ups in specialist care and are thereby expected to be correctly de ned in this registrybased study.…”
Section: Discussionmentioning
confidence: 94%
“…(5) Internationally, the use of digital platforms as a tool for health education in patients with DM has been the object of several studies, which has highlighted the benefits of this use. (6)(7)(8)(9)(10)(11) For example, it has been identified that an important percentageabout 30% -of patients with 1DM and 2DM use Facebook® as the first source of information about the disease. (5) This tool has been used to share personal clinical information, request specific disease guidance and feedback, and also receive emotional support.…”
Section: Introductionmentioning
confidence: 99%
“…(11,12) Finally, the results of studies point to the possibility of health professionals to use social media to provide support for the education of patients with DM and their caregivers, disseminating useful and safe knowledge and information related to disease treatment and control. (7,11) Given the above and considering the high prevalence of 1DM, there is complexity in the management of this condition, especially by young people. There is a low demand for health services from them, (13) making it imperative to develop actions that overcome traditional care.…”
Section: Introductionmentioning
confidence: 99%